(3cJGH GbdjOS aj GdXGgQGJs - (3GbdjOSs
(3ChdgG (B:s
(3ef Cgd Cf GdchGcH GdJGeI jXgQ WGdYg ef ehVY hGMO hCf CHYGOgG ai JMQjcgG ef GdeTQb Edi GdeZQH s
(3BNQgG (B:s
(3NW eYOd GdfgGQ Edi eG jdi GdefbdH GdTJhi Je cJGH ChbdjOS ai GdXGgQGJ ef Gdadc s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1436s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3Gdadcs